Islamic Worldview sebagai Solusi Krisis Moral Remaja - Yaman, Nur; Yadi, Yadi; Sumiran, Sumiran (TSAQOFAH, 2025)
The moral challenges faced by adolescents in the era of globalization and modernization are increasingly complex, marked by tendencies toward hedonism, deviant behavior, verbal aggression, and identity crises. These issues are exacerbated by the lack of internalization of religious values in daily life. This article aims to examine the Islamic worldview as a foundational framework for fostering moral awareness and behavior in adolescents based on Islamic teachings. The study adopts a descriptive qualitative approach through a literature review, analyzing scholarly sources from various relevant academic references. The findings indicate that the Islamic worldview offers a holistic and transcendental moral framework capable of guiding adolescents toward ethical, responsible behavior aligned with Islamic principles. This worldview emphasizes the interconnectedness of spiritual, social, and individual aspects of life, thereby shaping a well-rounded Islamic character. Strengthening the Islamic worldview requires synergy among families, educational institutions, and social media platforms that convey positive values. The article recommends the implementation of a comprehensive and continuous educational model to develop a morally resilient and spiritually strong Muslim youth capable of navigating contemporary challenges.